Medicolegal Approach of a Scald Burn Case in the School - Ahsen Kaya; Uğur Ata; Hülya Güler; Ender Şenol; Ekin Özgür Aktaş (Galenos Yayinevi, 2021)
The school environment is the place where children mostly are away from parental supervision for the first time and for a long period of time. Children may be injured by accidents like burns at the school. Thus, making them vulnerable when security measures are not taken accordingly. This study aimed to discuss the trauma severity and medicolegal aspects of a scald injury in the school. This is a case of a 7-year-old male who had burn injury by spilling hot water at the school canteen with a medicolegal perspective by related literature. A second degree burn that covers about 30% of his body surface was determined in his first medical records. Sepsis and renal insufficiency had been developed in the process. Three years after the accident, his tissue losses and psychological symptoms due to the accident were examined for his forensic report. Findings conspicuously showed that accidents might cause permanent physical and psychological damages in individuals, their families and also significant costs for the society. Accidents and their negative impacts may be prevented by simple measures like educating the school staff, families and children about first aid for burn injuries. These impacts are subject to both punishment and compensation lawsuits. In this regard, expert witnesses and forensic reports are important to prevent miscarriages of justice.